TELAAH FEMINISME DALAM PUISI IMPRESSIONS FROM AN OFFICE KARYA N. JOSEFOWITZ - Amin Khudlori (Universitas Aki, 2018)
Poetry can be used as a mean to tell what someone feel or thought. It is occasionally the experience of the author. The writer uses two methods in conducting this study, they are data collection and approach methods. The writer uses the library research method for the data collection method to collect the data needed to support the discussion. The objective or the structural approach method and feminism approach method are used to comprehend and to obtain deeper understanding of the poem. The writer wants to achieve some objectives in conducting this study. Some of the objectives are to get deeper understaanding on feminism found in N. Josefowitz’ poetry Impressions from an Office, to find out the impacts of social condition and the feminism movement effects growing in America on the people, and to find out the implicit meanings of N. Josefowitz’ poetry above. Feminism is a kind of social movement which aims to get gender equality for male and female. Besides that, it is also a literary approach. The feminism principle as literary approach is based on how literary work reflects gender aspects. A poetry written by N. Josefowitz as a kind of literature will be used in this paper as an object of study. By analyzing that poetry, we will understand how feminism as a social movement affects literary approach.Keywords: feminism, gender, equality, social, poetry